Pengaruh Pendidikan Kesehatan terhadap Pengetahuan, Sikap, dan Frekuensi Konsumsi Makanan Jajanan - Wulan Angraini; Betrianita Betrianita; Bintang Agustina Pratiwi; Riska Yanuarti; Pebi Fermana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of health education with audio-visual methods on knowledge, attitudes, and frequency of consumption of street food in students of SDN 52 Kota Bengkulu in 2018. This type of prospective experimental research is Quasi Experimental Design with Nonequivalent Control Group Design. The statistical test results obtained p-value 0.002 for knowledge variables, 0.225 for attitudes and 0.84 for frequency. In conclusion, there is a difference in the average knowledge before and after being given audio-visual education. There was no difference in the average attitude and frequency of consumption of snacks before and after being given audio-visual education at 52 Elementary Schools in Bengkulu City. Keywords: Snack Frequency, Health Education, Knowledge, Attitude